Determination of optimal operation time for the management of acute cholecystitis: a clinical trial - Oymaci, Erkan; Ucar, Ahmet Deniz; Yakan, Savas; Carti, Erdem Baris; Coskun, Ali; Erkan, Nazif; Yildirim, Mehmet (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Although all studies have reported that laparoscopic cholecystectomy (LC) is a safe and effective treatment for acute cholecystitis, the optimal timing for the procedure is still the subject of some debate. Aim : This retrospective analysis of a prospective database was aimed at comparing early with delayed LC for acute cholecystitis. Material and methods : The LC was performed in 165 patients, of whom 83 were operated within 72 h of admission (group 1) and 82 patients after 72 h (group 2) with acute cholecystitis between January 2012 and August 2013. All data were collected prospectively and both groups compared in terms of age, sex, fever, white blood count count, ultrasound findings, operation time, conversion to open surgery, complications and mean hospital stay. Results: The study included 165 patients, 53 men and 112 women, who had median age 54 (20–85) years. The overall conversion rate was 27.9%. There was no significant difference in conversion rates (21% vs. 34%) between groups (p = 0.08). The operation time (116 min vs. 102 min, p = 0.02) was significantly increased in group 1. The complication rates (9% vs. 18%, p = 0.03) and total hospital stay (3.8 days vs. 7.9 days, p = 0.001) were significantly reduced in group 1. Conclusions: Early LC within 72 h of admission reduces complications and hospital stay and is the preferred approach for acute cholecystitis.